High Aerobic Intensity Training and Psychological States in Patients with Depression or Schizophrenia - Heggelund, Jørn; Kleppe, Kim Daniel; Morken, Gunnar; Vedul-Kjelsås, Einar (Frontiers in Psychiatry, 2014)
Aim: To explore changes in psychological states in response to a bout of high aerobic intensity training (HIT) in patients with depression or schizophrenia compared to healthy individuals. Methods: After familiarization training of HIT, 20 patients with schizophrenia, 13 patients with depression, and 20 healthy individuals performed a no-training day followed by a training day. HIT was 4 x 4 minute intervals at 85-95% of peak heart rate, intermitted by 3 minutes active rest periods at 70% of peak heart rate. Self-evaluation questionnaires of positive affect, negative affect, state anxiety, well-being, distress and fatigue were completed before training, 15 minutes after and 3 hours after training. The two latter measures were also completed the no-training day. Results: All three groups improved in positive affect and well-being 15 minutes after HIT (p<0.01), but only patients with depression had maintained the effect after 3 hours (p=0.007, p=0.012). The duration of the improved positive affect was longer in depression (p=0.002) and schizophrenia (p=0.025) than in healthy individuals (F2.50 = 5.83, p<0.01). Patients with depression or schizophrenia had reduced distress and state anxiety 15 minutes after HIT and 3 hours after HIT (p<0.05). The improvement in distress 15 minutes after HIT was larger in patients with depression (p=0.028) compared to healthy individuals (F2.50 = 5.05, p<0.01). No changes were found during the no-training day (p>0.05). Conclusion: HIT used as an acute intervention improved positive affect and well-being and reduced distress and state anxiety in patients with depression and schizophrenia. ClinicalTrials.gov identifier: NCT01310998.